Surface coating of carbon nanofibers/nanotubes by electrodeposition for multifunctionalization - Xing, H; Sun, L; Song, G; Gou, J; Hao, Y W (Nanotechnology, 2008)
Carbon nanomaterials in the form of paper sheets have been used as platforms to achieve multifunctionality. Combined with electrochemical deposition, room temperature synthesis of magnetic Ni coatings on individual carbon nanofibers (CNF) and/or carbon nanotubes (CNT) has been realized through solution penetration and ion diffusion. In addition to significant electrical conductivity improvement, the magnetic responses of the Ni coated carbon nanopaper sheets can be tuned within large ranges in terms of saturation magnetic field, remnant magnetization and coercivity. After being re-suspended in liquids, the magnetized CNFs/CNTs can be aligned with small external magnetic fields.